2021
DOI: 10.1002/uog.22151
|View full text |Cite
|
Sign up to set email alerts
|

Performance of six birth‐weight and estimated‐fetal‐weight standards for predicting adverse perinatal outcome: a 10‐year nationwide population‐based study

Abstract: Objective To evaluate three birth‐weight (BW) standards (Australian population‐based, Fenton and INTERGROWTH‐21st) and three estimated‐fetal‐weight (EFW) standards (Hadlock, INTERGROWTH‐21st and WHO) for classifying small‐for‐gestational age (SGA) and large‐for‐gestational age (LGA) and predicting adverse perinatal outcomes in preterm and term babies. Methods This was a nationwide population‐based study conducted on a total of 2.4 million singleton births that occurred from 24 + 0 to 40 + 6 weeks' gestation be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
29
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(40 citation statements)
references
References 45 publications
6
29
1
Order By: Relevance
“…Multiple single-country studies have compared Intergrowth-21st's newborn charts with national charts. Similar to our results, local birthweight charts [33] , [34] , [35] as well as Gardosi's customised model[ 36 , 37 ] have found that using Intergrowth-21st yielded a lower prevalence of SGA and a higher prevalence of LGA than national or customised charts. We add to this literature by showing that the differences in the prevalence of SGA and LGA when using international charts varied greatly between European countries and followed a geographic gradient from north to south.…”
Section: Discussionsupporting
confidence: 90%
“…Multiple single-country studies have compared Intergrowth-21st's newborn charts with national charts. Similar to our results, local birthweight charts [33] , [34] , [35] as well as Gardosi's customised model[ 36 , 37 ] have found that using Intergrowth-21st yielded a lower prevalence of SGA and a higher prevalence of LGA than national or customised charts. We add to this literature by showing that the differences in the prevalence of SGA and LGA when using international charts varied greatly between European countries and followed a geographic gradient from north to south.…”
Section: Discussionsupporting
confidence: 90%
“…39 Several studies have compared IG, WHO, Hadlock and local charts and have also reported low sensitivity of the IG charts for detecting SGA fetuses. 22,23,42 For instance, a UK study reported that the cut-off for the best sensitivity for SGA <10th percentile when specificity was set at 90% was the 11th percentile for Hadlock versus the 18th percentile for INTERGROWTH-21st. 23 Other studies comparing local EFW distributions to IG and WHO in China and Italy also noted important discrepancies in fit.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, it is important to be aware of the inaccuracy of EFW as measured by ultrasound and the matching of BW. Cohort studies on EFW reported a high intra-and interobserver variability and a detection rate of less than 50% of SGA newborns [34,35].…”
Section: Discussionmentioning
confidence: 99%